FAM222A encodes a protein which accumulates in plaques in Alzheimer’s disease - Tingxiang Yan (Nature Portfolio, 2020)
In this study the authors identify a possible link between the gene FAM222A and brain atrophy. The protein it encodes is found to accumulate in plaques seen in Alzheimer’s disease, and functional analysis suggests it interacts with amyloid-beta.